(untitled) (Prostor, 2024)
The Covid-19 pandemic has significantly changed the work perception and attitudes of employees. The goal of this research is to identify the experience of the beneficiaries and provide guidelines to develop an optimal model of the working environment during and in the post-pandemic period. The study is focused on an anonymous survey comprising 34 combined questions conducted online among 202 responders, including general questions, the issue of working conditions in offices, manner of transforming working conditions during the pandemic and personal perception of comfort. The questionnaire is also related to transitive solutions, work from home and the accentuation of a favourite manner of work upon the end of the pandemic. The results of the questionnaire together with theoretical analyses of this research may be useful for creating a good basis for the definition of optimal work spaces in the post-pandemic period, in order to further direct the development of resilient work spaces on the territory of Podgorica, as a case study. The study may be also applied to other contexts.